ANALISIS ISI INFOGRAFIS AKUN RESMI LINE KEMENTERIAN KOMUNIKASI DAN INFORMATIKA - Galih, Aulia (BACA: Jurnal Dokumentasi dan Informasi, 2021)
This research is conducted to find the contents of information in the form of infographics on the official LINE account of KEMKOMINFO and to find whether the infographics made have fulfilled its function as a means of information repackaging. In general, researchers conduct research on academic implications and the object of the research is academics, but this research is different, the object of this research is official LINE account of KEMKOMINFO which is a government institution. This research uses descriptive qualitative methods with content analysis techniques without using respondents or informants as research objects. Content analysis for infographics on the official LINE KEMKOMINFO account was carried out for 6 months in October 2019 to March 2020. There are 9 information displays on the official LINE account of KEMKOMINFO: (1) latest news on the most popular issues in Indonesia; (2) information on specific themes; (3) information regarding the results of the activity conducted by government institutions; (4) information regarding KEMKOMINFO's clarification of news and issues circulating in public; (5) congratulory message at certain moments; (6) quiz about knowledge related to Indonesia; (7) information regarding procedures in the management of government-related matters; (8) the game of finding words based on clues; (9) word equivalents or translate. To facilitate the dissemination of information to the public, the Ministry of Communication and Information Technology (KEMKOMINFO) chose to use infographics because information in visual form is more attractive and easily understood by the general public, especially by the younger generation as readers.